Studi pemisahan senyawa polyaromatichydrocarbon (pah) secara kromatografi cair=The Study of Separation Process of Poly aromatic Hydrocarbons by Liquid Chromatography - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Polyaromatic Hydrocarbons (PAHs) are a class of organic chemicals, composed of fused benzene rings, occured in the environment due to incomplete combustion of fossil fuels. Health concerns are focussed to the metabolite transformation of PAHs, which is carcinogenic, mutagenic and terratogenic. Due to their hydrophobidty. so there are probable into human food chain. The aims of this research is to study resolution of eight component mixture PAHs (fluoranthene, pyrene, benzo(a)anthrasene, chrysene, benzo(k)fluoranthene, benzo(a)pyrene, perylene, and dibenz(a,h) anthrasene) by High Performance Liquid Chromatography (HPLC). The result shown that optimally condition of HPLC as follows: stationary phase is Clg with size particle 5 mm, column length 20 cm and inside diameter lcm. Mobile phase is acetonitrile-water with gradien elution programme from 70% of acetonitrile in water to 80%. Detector is uv-vis spectrophotometer at 254nm. Resolution parameters by HPLC are k': 4,2 - 9,9